Indian foreign policy: The Modi era - Pant, Harsh V (New Delhi Har-Anand Publications, 2022)
Indian foreign policy has undergone a remarkable transformation in a short span of five years since the coming to office of the Narendra Modi government in May 2014. This is reflected in the academic and policy debates that have emerged in the last few years. No Prime Minister before has generated the kind of voluminous literature that Prime Minister Modi's foreign policy has in such a short span, forcing even the critics to concede that something has indeed shifted on the foreign policy front. This book is a collection of author's articles written over a period of five years covering various aspects of Modi government's foreign policy. They provide a vivid trajectory of the evolution of Indian foreign policy priorities over the last five years and underscore the shifts and continuities in Prime Minister Modi's global outreach. The writings in this volume cover the author's assessment of the Modi government's foreign policy since May 2014, thereby allowing the readers to engage with the broader arc of Indian diplomacy. Hopefully, it will also allow academics and practitioners to have a more meaningful debate on the substantive shifts in Indian foreign policy over the last few years.
Keywords: Prime Minister; Indian Foreign Policy; Narendra Modi